Analysis Of Hospital Readiness For The Implementation Of Standard Inpatient Care Class (KRIS): Literature Review: English - Saleh, Ria Amalia; Rosyidah, Rosyidah; Hidayat , Muhammad Syamsu (Jurnal EduHealth, 2024)
Health development aimed to improve access and quality of health services, yet 4.5 billion people globally and 2.9 million rural residents in Indonesia still lacked adequate access. The JKN Program strived to equalize health services, despite facing challenges such as complex registration and access inequalities. To enhance inpatient care quality, the Standard Inpatient Care Class (KRIS) system was implemented with 12 criteria. Although 81% of regional hospitals showed readiness for KRIS, many still required infrastructure adjustments. This study analyzed hospital readiness in implementing KRIS and provided recommendations to enhance its implementation effectiveness. The research utilized a literature review with a PRISMA approach. Google Scholar and PubMed search engines were used. After removing duplicates and filtering articles, eight relevant articles were selected and evaluated using Mendeley software. The research findings indicated variations in hospital readiness to meet Standard Inpatient Care Class (KRIS) requirements. Pertamina Bintang Amin Hospital only met 30% of the KRIS standards, while regional public hospital dr. Moch Anshari Saleh Banjarmasin achieved 85% readiness. Regional public hospital karanganyar and hospital Bhayangkara Medan faced challenges in policy socialization and infrastructure, while hospitals in Tangerang and Purwakarta districts struggled with meeting intensive care and isolation room standards. This study highlighted the need for infrastructure and facility improvements, as well as policy socialization for KRIS to achieve full standards. Hospital readiness for KRIS varied, with main challenges in infrastructure, facilities, socialization, as well as budgetary and funding constraints. The government and BPJS Kesehatan should monitor hospital readiness and subsidy mechanisms periodically.